Evaluation and recommendations for greater accessibility of colour figures in ornithology. (17th October 2020) - Pollet, Ingrid L.; Bond, Alexander L.
Abstract : People who are colour‐blind or have some form of colour vision deficiency form an invisible minority and scientists should strive to be as inclusive as possible. We reviewed 2873 figures published in 2019 from 1031 scientific papers in 27 ornithological journals to determine those that were colour‐blind compatible, and those that were black‐and‐white printer friendly. About 26% of the published figures were in colour, and while most were colour‐blind compatible, only 60% of them were black‐and‐white printer friendly. Ensuring figures in all forms of scientific communication can be interpreted by readers who are colour‐blind, and can be printed in black‐and‐white will improve the accessibility of ornithological research.